THE POPULATION DYNAMIC OF BANANA PRAWN (Penaeus merguiensis de Man) IN TANAH LAUT WATERS, SOUTH KALIMANTAN - Ali Suman; Ap’idatul Hasanah; Tri Ernawati; Andina Ramadhani Putri Pane (Research Center for Fisheries, 2017)
Scientific advices on population dynamic of banana prawn (P. merguiensis de Man) are required as an input to support an apropriate fisheries management. This study aims to identify the population parameters of the banana prawn in Tanah Laut waters. The study was conducted in Tanah Laut based on monthly enumeration data (January to November 2016). Results has been shown that the length size of carapace at first maturity of banana prawn was 43.39 mm. Sex ratio of males and females was 1 : 0.8. The chi square test indicated that comparison of male and female of the banana prawn was significantly different. It means that there was not balance in number between males and females. The spawning season of banana prawn in Tanah Laut waters happened throughout year and reached the peak on November (south-east monsoon). The growth parameter of banana prawn was 1.05/year with maximum carapace length (Loo) of 55.0 mm. Instantaneous total mortality (Z) and natural mortality (M) were 6.05/year and 1.58/year, respectively. While fishing mortality (F) and exploitation rate (E) respectively were 4.47/year and 0.74/year respectively. The exploitation rate of banana prawn in Tanah Laut waters was high. Therefore, fishing effort of the banana prawn in that waters should be reduced to about 48 % for next coming year.